Analysis of the relationship between oil prices and the broad money supply in light of sustainable development in Iraq for the period (2004-2022) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
After 2004, Iraq resumed the production and export of crude oil after a blockade that lasted more than a decade. Iraq was able to achieve good financial surpluses from the sale of crude oil, but excessive reliance on oil revenues caused the destruction of the remaining economic activities and the economic dependency deepened further, until oil prices became It greatly affects most economic variables, including the money supply. The problem of the research is that excessive rentierism in the Iraqi economy established a special relationship between oil prices and the money supply, which contributed greatly to the fluctuations in the money supply during the research period, which in turn contributed to monetary turmoil that forced the Central Bank of Iraq to adopt several mechanisms in order to avoid the severity of these fluctuations, which undermined most of the plan’s Sustainable economic development. The research found that there is a temporal synchronization in the specific path of oil price growth rates and the growth rate of the broad money supply in Iraq. The research recommended adopting an approach to encourage investments in economic sectors to increase their activity and reduce the concentration of the oil sector in the local economy.